x+64=3x-26

Simple and best practice solution for x+64=3x-26 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+64=3x-26 equation:


Simplifying
x + 64 = 3x + -26

Reorder the terms:
64 + x = 3x + -26

Reorder the terms:
64 + x = -26 + 3x

Solving
64 + x = -26 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
64 + x + -3x = -26 + 3x + -3x

Combine like terms: x + -3x = -2x
64 + -2x = -26 + 3x + -3x

Combine like terms: 3x + -3x = 0
64 + -2x = -26 + 0
64 + -2x = -26

Add '-64' to each side of the equation.
64 + -64 + -2x = -26 + -64

Combine like terms: 64 + -64 = 0
0 + -2x = -26 + -64
-2x = -26 + -64

Combine like terms: -26 + -64 = -90
-2x = -90

Divide each side by '-2'.
x = 45

Simplifying
x = 45

See similar equations:

| 2x+5=x+59 | | x^2+40x+400=0 | | x-24=64-10x | | 6z=8+2z | | 3x+71=5x-37 | | 5m+35=15 | | 5m-4p=-2 | | x+27=2x-17 | | 5(2x-1)+4=9x-7 | | 23x+8=(-7)+18x | | 4(5+c)=3(c-5) | | 10+4t=5(t+2) | | 7a+17+11=0 | | 3-4x=10+3x | | -12y+3=13 | | 3x-35=2x+52 | | 14x+24=12x+28 | | -14n+18=-12n-16 | | -2y-10=4y+32 | | x^2-4x-m=0 | | 10c+7=-2c+16 | | (x^3-1)(x^2+6x)=0 | | 4i*3= | | 41*3= | | x^2+8x+42=0 | | 4x^3+3x^2-8x-6=0 | | -3+12=12x-4-11x | | -10k-24=3k-96-5k | | 16x^2+8x-18=0 | | 7y-9y=-9-13 | | 11x+55=0 | | 11x+55=o |

Equations solver categories